PRELIMINARY LABORATORY EVALUATION OF RAPID DIAGNOSTIC TEST PROTOTYPE TO DETECT HBsAg IN WHOLE BLOOD AND SERUM - Qurnianingsih, Ema; Wungu, Citrawati Dyah Kencono; Amin, Mochammad; Setyawati, Dewi; Yasan, Yanna Debby Restifanny; Lukitasari, Lina; Lusida, Maria Inge; Soetjipto, Soetjipto (Folia Medica Indonesiana, 2025)
Chronic hepatitis B virus (HBV) remains a major global health issue,[-10pc]AU: Please provide ORCID ID for all authors.[-7pc]AU: Please provide affiliation’s for all authors. with over 250 million people affected worldwide. In Indonesia, HBV prevalence has declined from high to moderate endemicity, but challenges persist due to regional disparities, risk of mother-to-child transmission, and the predominance of B3 and C1 sub-genotype. Despite available preventive measures and diagnostic tools, approximately 90% of cases remain undiagnosed, particularly in low-resource settings, indicating the need for improved screening and control strategies. Therefore, this study aims to conduct preliminary performance tests of KODC hepatitis B surface antigen (HBsAg) (rapid diagnostic test (RDT) prototype) produced by Konimex on serum and whole blood samples. Performance was assessed through sensitivity, precision, specificity, and comparative testing against commercial RDT. The results obtained were visually interpreted by 2 independent readers. KODC HBsAg RDT demonstrated a detection limit of 50 IU/ml in serum and 400 IU/ml in whole blood. Precision testing showed high reproducibility (RSD <3.02%), with no cross-reactivity against other pathogens. Compared with a commercial RDT, it showed equivalent performance in serum and superior specificity in whole blood. In addition, predictive value analysis confirmed excellent accuracy, with Positive predictive value (PPV) and negative predictive value (NPV) >99% in both sample types. Therefore, KODC HBsAg RDT prototype showed comparable performance to commercial tests with good sensitivity, precision, and specificity, indicating its potential as a practical tool for HBV screening in resource-limited settings.